2021
DOI: 10.1002/jemt.23974
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the morphological and fractal behavior at nanoscale of patterning lines by scratching in an atomic force microscope

Abstract: In this work, the topographical effect of the scratching trajectory and the feed direction on the formation of lithographed lines on the (001) InP surface was investigated using an atomic force microscope (AFM) tip-based nanomachining approach.Nanoscratching tests were carried out using the sharp face of a diamond AFM tip in contact mode. From the topographic maps obtained by AFM, several morphological and fractal parameters were obtained and analyzed. Surface morphology presented a surface smoothing for surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The peak at 389 nm (3.19 eV) is assigned to the near-band-edge (NBE) UV emission or due to the recombination of holes (h + ) generated by photons with a specific defect charge state. The emissions at 405 nm (3.06 eV) and 420 nm (2.95 eV) are associated with deep-level emissions, which originate from oxygen interstitial (O i ) and oxygen vacancies (V O ) for both ZnO and α-Fe 2 O 3 crystals [91][92][93]. The blue emission at 468 nm (2.65 eV) is assigned to V O defects in ZnO crystals [94] or due to the 6 The distinctive structural and morphological characteristics of BFDW undoubtedly underlie its optical properties, as depicted in Figure 4.…”
Section: Characterization Of Bfdw Powdermentioning
confidence: 99%
“…The peak at 389 nm (3.19 eV) is assigned to the near-band-edge (NBE) UV emission or due to the recombination of holes (h + ) generated by photons with a specific defect charge state. The emissions at 405 nm (3.06 eV) and 420 nm (2.95 eV) are associated with deep-level emissions, which originate from oxygen interstitial (O i ) and oxygen vacancies (V O ) for both ZnO and α-Fe 2 O 3 crystals [91][92][93]. The blue emission at 468 nm (2.65 eV) is assigned to V O defects in ZnO crystals [94] or due to the 6 The distinctive structural and morphological characteristics of BFDW undoubtedly underlie its optical properties, as depicted in Figure 4.…”
Section: Characterization Of Bfdw Powdermentioning
confidence: 99%
“…In other words, this means that these samples have the distribution of topographical heights evenly distributed along the surface, which is a remarkable characteristic of these samples. Some previous reports have associated the topographical uniformity of the rough profile with some physical properties, e.g., friction, wear, and adhesion [51][52][53]. A higher topographical entropy value suggests that the possibility of material failure is minimized.…”
Section: Analysis Of the Films' Spatial Microtexturementioning
confidence: 99%
“…Second, when performing nanolithography on crystalline materials, depending on the geometry of the tip, fractures can occur resulting in the formation of irregular cracks on the edges of the features. [14][15] These defects even if they are subsurface, can have important undesired effects in the resulting lithograph. It has been demonstrated that subsurface defects could alter the performances of GaAs-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Additionally, because nanoscratching results in material displacement rather than material removal, it gives rise to hillock formations surrounding the features as well as debris within features. [14,17] The consequence is a much-increased surface roughness and a lack of control over the shape and edge-sharpness of the desired features.…”
Section: Introductionmentioning
confidence: 99%